1984
DOI: 10.7164/antibiotics.37.691
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of aklanonic acid, a potential early intermediate in the biosynthesis of anthracyclines.

Abstract: The close structural relationship of this compound (aklanonic acid, Ia, Fig. 1) to anthracyclinones induced us to attempt its biotransformation to anthracyclines by daunorubicin-negative mutants derived from different daunorubicin producing organisms. The results of our experiments provided evidence that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…An inability of 2-OH-aklanonic acid to enter the cells is unlikely, because Eckardt e t al. (1985b) and Wagner et al (1984) succeeded in converting aklanonic acid to aglycones by biotransformation.…”
Section: Discussionmentioning
confidence: 99%
“…An inability of 2-OH-aklanonic acid to enter the cells is unlikely, because Eckardt e t al. (1985b) and Wagner et al (1984) succeeded in converting aklanonic acid to aglycones by biotransformation.…”
Section: Discussionmentioning
confidence: 99%
“…caesius 2118 were found to produce anthracyclines and anthracyclinones when aklanonic acid was added t o the cultures under the conditions found t o be optimal in previous experiments with mutants of Str. griseus (WAGNER et al 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous experiments with blocked mutants of Streptomyces griseus showed that the anthracyclinone-related metabolite aklanonic acid with its incomplete carbon skeleton can serve as a precursor in the biosynthesis of structurally different types of anthracyclinones (WAGNER et al 1984, ECKARDT et al 1985. We, therefore, were interested t o find out whether aklanonic acid is also transformed by other species of Streptomyces known as producers of anthracyclines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From biosynthetic studies, many intermediates have been isolated and their roles in the biosynthesis of anthracyclines have been clarified (16,31,35). There is also some understanding of the enzymatic steps in the biosynthetic pathway (11).…”
mentioning
confidence: 99%